Leafcutter Ant Nests Inhibit Low-Intensity Fire Spread in the Understory of Transitional Forests at the Amazon's Forest-Savanna Boundary - Karine S. Carvalho; Ane Alencar; Jennifer Balch; Paulo Moutinho (Psyche: A Journal of Entomology)
Leaf-cutter ants (Atta spp.) remove leaf litter and woody debris—potential fuels—in and around their nests and foraging trails. We conducted single and three annual experimental fires to determine the effects of this leaf-cutter ant activity on the behavior of low-intensity, slow-moving fires. In a transitional forest, where the southern Amazon forest meets the Brazilian savanna, we tested whether leaf-cutter ant nests and trails (i) inhibit fire spread due to a lack of fuels, and (ii), thereby, reduce the total burned area during these experimental low-intensity fires, particularly at forest edges where leaf-cutter ant abundance was higher. Fine-medium fuel mass increased with an increase in distance from ant nest, and the mean area of bare soil was greater on nests than on the forest floor. Between 60 to 90 percent of the unburned area was within 30 m of ant nests, and burned area significantly increased with increasing distance to ant nests. In addition, the number of ant nests declined with increasing distance from the forest edge, and, with exception of the first experimental fire, burned area also increased with increasing distance from the edge. The present study provides new insight to fire ecology in Amazon environments.